Correlation of load drop and crack initiation criteria in fatigue life experiments of metallic materials. (15th June 2021) - Heckmann, Klaus; Sievers, Jürgen; Schopf, Tim; Lücker, Lukas; Schmiedt-Kalenborn, Anke; Walther, Frank; Starke, Peter; Acosta, Ruth; Boller, Christian
Highlights: The influence of crack location on crack size in fatigue tests is investigated. A given load drop in a test corresponds to a range of possible crack depths. Initiated fatigue cracks may have a crack depth larger or smaller than 3 mm. The derived crack size assumptions are relevant in fracture mechanical assessments. Abstract: The simulation and assessment of fatigue damage of metallic materials are strongly dependent on the definition of critical damage initiation, i.e. the formation of a crack after a certain number of cycles under fatigue loading. To get this described in an appropriate way classical fatigue analysis needs to be combined with fracture mechanics to obtain a realistic size of an initiating macro crack in a component in the end. Ultimately, this size depends on the procedure of how fatigue life curves are generated from the fatigue tests performed. In this paper strain-controlled fatigue tests and fractographic results have been combined with a computational assessment to better understand the relationship between a traditional load drop criterion characterizing the size of a crack being initiated. It is stated that the location of an initiating crack versus the location of an extensometer applied to the specimen can have an influence on the crack size being initiated and thus the fatigue life for a load drop criterion being fixed. A relationship is proposed to link a crack size dependent on the fatigue test evaluation scheme with the fatigue life, which can be used in engineering assessments. The relevance of practical application cases is discussed.